Comparison of Frequently Used Fever Measurement Methods: Which One is the Best? - Aydın, Cansu; Bayhan, Gülsüm İclal (Journal of Pediatric Infectious Diseases, 2024)
Objective Peripheral measurement sites and methods used to determine core body temperature were investigated, as there is still debate about which noninvasive core body temperature measurement method is the most valuable and accurate for each age group.Methods Children aged 1 to 36 months were included in the study. The temperature was measured from the forehead (noncontact cutaneous), temporal artery (TA), axilla, and rectum. The rectal measurement was accepted as the reference measurement. A rectal temperature of ≥38.3°C was defined as fever.Results The noncontact cutaneous, axillary, and TA measurements were 1.2, 1.1, and 0.7°C lower than rectal measurements, respectively (p < 0.001, <0.001, <0.001). The TA and noncontact cutaneous measurements demonstrated a moderate positive correlation with rectal measurements, whereas a strong positive correlation was seen between the axillary and rectal measurements. A cutaneous temperature of 37.8°C was found to have a positive predictive value (PPV) of 100%, negative predictive value (NPV) of 81%, sensitivity of 34%, and specificity of 100% for detecting fever. The respective values were 80, 79.4, 23.5, and 98% for an axillary temperature of 37.5°C, and 90, 86.2, 52.9, and 98% for a TA temperature of 38°C.Conclusion The commonly used fever measurement methods have high PPV and NPV and specificity but low sensitivity.
Keywords: fever; forehead; temporal artery; axilla; rectum